Peran Guru ISMUBA Dalam Membiasakan Siswa Shalat Fardhu Berjama’ah di SMK Muhammadiyah 1 Wates - Sendi Nurtanti (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research discusses the role of ISMUBA teachers in getting students used to praying in congregation. This research aims to describe the role, implementation and impact of the ISMUBA teacher's role in familiarizing students with congregational prayer at Muhammadiyah 1 Wates Vocational School. The research method used is a descriptive method with a qualitative approach. And data collection instrument techniques are through observation, interviews and documentation. The research results show that the role of ISMUBA teachers is more important than general subject teachers. This is because general subject teachers usually tend to be indifferent to the implementation of congregational prayers that occur in the school environment. The success of the ISMUBA teacher's role is also supported by students' awareness of the benefits of congregational prayer.